Hot to the touch - Burton, Jaci (Burton, Jaci. Brotherhood by fire., 2019)
OLD FLAMES BURN WHITE-HOT. Firefighter Jackson Donovan doesn't look back--as a rule. So when his past comes roaring back to life in the form of not-so-damsel-in-distress Becks Benning, the last thing he wants to do is relive old times. No matter how tempting she makes it seem.... Now, thanks to his two interfering brothers, Becks is living with Jackson while she looks for a new place and tries to pick up the pieces of her tattoo business that went up in flames. Which means a grown-up, smokin'-hot Becks is in his house, digging up old wounds. And despite his better judgment, the more time he spends with this smart, artistic, incredible woman, the more he wants her in his bed--and in his future. Becks always had it bad for Jackson. Unfortunately for her, not much has changed. He's still honorable, hard-working, sexy as sin--and closed-off. But there's more than one way to get to a man's heart, and if Jackson doesn't want to recall old memories, she'll just have to help him make new ones. Because now that she's found Jackson again, she's not letting him go.--